Next-Generation Sequencing Reveals the Progression of COVID-19 - Chen, Xiaomin; Kang, Yutong; Luo, Jing; Pang, Kun; Xu, Xin; Wu, Jinyu; Li, Xiaokun; Jin, Shengwei (Frontiers in Cellular and Infection Microbiology, 2021)
The novel coronavirus SARS-CoV-2 (causing the disease COVID-19) has caused a highly transmissible and ongoing pandemic worldwide. Due to its rapid development, next-generation sequencing plays vital roles in many aspects. Here, we summarize the current knowledge on the origin and human transmission of SARS-CoV-2 based on NGS analysis. The ACE2 expression levels in various human tissues and relevant cells were compared to provide insights into the mechanism of SAS-CoV-2 infection. Gut microbiota dysbiosis observed by metagenome sequencing and the immunogenetics of COVID-19 patients according to single-cell sequencing analysis were also highlighted. Overall, the application of these sequencing techniques could be meaningful for finding novel intermediate SARS-CoV-2 hosts to block interspecies transmission. This information will further benefit SARS-CoV-2 diagnostic development and new therapeutic target discovery. The extensive application of NGS will provide powerful support for our fight against future public health emergencies.